Growth Analysis and Identification of Viral Diseases (WSSV, IHHNV, IMNV) and AHPND in White Shrimp (Litopenaeus vannamei) Cultivation using Millennial Shrimp Farming (MSF) System - Zulkisam Pramudia; Abd Rahem Faqih; Agus Fery Setiawan; M. Amenan; Andi Kurniawan (Jurnal Pembangunan dan Alam Lestari)
The aquaculture sector continues to be developed to support sustainable development in Indonesia. One of the efforts made to develop sustainable aquaculture in the fisheries sector is the application of sustainable technological innovations to increase aquaculture productivity. The Millennial Shrimp Farming (MSF) system for white shrimp cultivation has developed to achieve increased production that can be carried out on limited land and relatively small business capital. However, although the MSF system has been widely carried out, studies reporting on monitoring shrimp growth and viral diseases in the MSF system in Indonesia have not been widely reported. This study aims to monitor the growth of white shrimp and the presence of viral diseases during white shrimp culture using the MSF system in Indonesia. This study was conducted in 3 MSF ponds by calculating growth and identifying viral diseases, namely White Spot Syndrome Virus (WSSV), Infectious Hypodermal and Hematopoietic Necrosis Virus (IHHNV), Infectious Myo Necrosis Virus (IMNV), and Acute hepatopancreatic necrosis disease (AHPND) with using the Polymerase Chain Reaction (PCR) method. Based on the results, the growth parameters observed on the Day of Culture (DOC) 30, 37, 44, 51, 58, 65, and 72 in the three ponds had an average weight above the standard weight compared to the Indonesian Nasional Standard (SNI 01-7246-2016) regarding the production of white shrimp in ponds with intensive technology. Meanwhile, the results of identifying viral diseases (WSSV, IHHNV, IMNV) and AHPND on DOC 1, 7, 42, 66, and 72 all showed negative results. The results above indicate that the cultivation of white shrimp with the MSF method showed optimum results for growth parameters, and no viral disease was identified during cultivation.